Conflict and housing, land and property rights : a handbook on issues, frameworks, and solutions - Leckie, Scott (Cambridge books online., 2011)
"Housing, land and property (HLP) rights, as rights, are widely recognized throughout international human rights and humanitarian law and provide a clear and consistent legal normative framework for developing better approaches to the HLP challenges faced by the UN and others seeking to build long-term peace. This book analyses the ubiquitous HLP challenges present in all conflict and post-conflict settings. It will bridge the worlds of the practitioner and the theorist by combining an overview of the international legal and policy frameworks on HLP rights with dozens of detailed case studies demonstrating country experiences from around the world. The book will be of particular interest to professors and students of international relations, law, human rights, and peace and conflict studies but will have a wider readership among practitioners working for international institutions such as the United Nations and the World Bank, non-governmental organizations, and national agencies in the developing world"--Provided by publisher